The research aims to determine the influence of brand community on brand loyalty as mediated by the value creation practice of Nikon products on the brand community of Nikon team. This explanatory research explains causal relationship between the variables through hypothesis testing. The research samples are 150 Nikon Team community members who have been joining the community for at least 3 months. The hypotheses are tested through t-test, and the data are analyzed by multiple linear regression - Putro, Bagus Setio Widiyo (Jurnal Ilmiah Mahasiswa FEB, 2017)
The research aims to determine the influence of brand community on brand loyalty as mediated by the value creation practice of Nikon products on the brand community of Nikon team. This explanatory research explains causal relationship between the variables through hypothesis testing. The research samples are 150 Nikon Team community members who have been joining the community for at least 3 months. The hypotheses are tested through t-test, and the data are analyzed by multiple linear regression method using SmartPLS 3.0. The results of the study show that the t-statistics of brand community towards brand loyalty is 5.740 and of brand community towards value creation practice is 10.198. The value of t-statistic relationship between value creation practice and brand loyalty is 6.065, and that of t-statistic value in the test sobel is 6.125 for all variables, which indicates that they have more value for t-table 1.96. the calculation also shows that r2 value of brand loyalty is 0.507, which means that brand loyalty is influenced by brand community for 50.7%, and the value creation practice variable is 0.419, which means that the value creation practice is influenced by brand community for 41.9%.KÐµywords: Brand Community, Value Creation Practice, Brand Loyalty